TINJAUAN YURIDIS KEABSAHAN KLAUSUL TENTANG PEMINDAHAN OBJEK JAMINAN UTANG-PIUTANG BERUPA HAK ATAS TANAH KEPADA PIHAK KREDITUR DALAM PUTUSAN AKTAPERDAMAIAN : (Studi Kasus Putusan Pengadilan Agama Banyuwangi Nomor 3308/Pdt.G/2018/PA.Bwi) - Nugroho Utomo; Pasaribu, Agnes; Mulyanto, Rudi (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
Juridical Review Of The Validity Of The Clause On The Transfer Of The Object Of Guarantee Of Debts In The Form Of Land Rights To The Creditors In The Deed Ruling Peace (Case Study of Banyuwangi Religious Court Decision No. 3308/Pdt.G/2018/PA. Bwi). Explains that judges are obliged to recommend the litigants to take the peace procedure first. The resulting Peace Deed decision is expected to be in line with and not in conflict with the applicable laws and regulations, moreover, the peace deed decision is equated in power with a decision that has permanent legal force (Res Judicata). As is the case with an agreement regarding the transfer of the object of collateral for debts to the creditor if the debtor defaults in the decision on the peace deed. Law No. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land limits matters relating to the promise of ownership of objects as collateral for debts. The formulation of the problem in this research is: How is the validity of the clause regarding the transfer of the object of collateral for debts in the form of land rights to the creditor in the Decision on the Deed of Peace? and What are the legal consequences of the Decision on the Peace Deed Number 3308 / Pdt.G / 2018 / PA.Bwi? The type of research used in this study is a normative juridical approach, which is to analyze the problem from the point of view of civil law. In this study, using a case approach and a legal approach, the case approach is to examine cases related to the problems faced which have become court decisions and have legal force. The results of the study conclude that, the Decision of the Deed of Peace which regulates the transfer of objects of guarantee of debts to creditors if the debtor defaults is contrary to Article 12 of UUHT and is not in line with several jurisprudence, and therefore violates the objective requirements of Article 1320 of the Civil Code, namely a Halal Cause. So that the Decision on the Peace Deed becomes materially flawed and is not legally valid. Then, the legal consequences of the decision on the Peace Deed Number 3308 / Pdt.G / 2018 / PA.Bwi which contain material defects, in this case violate the objective requirements of article 1320 of the Civil Code, namely a Halal Cause. So the decision of the peace deed becomes null and void and the decision cannot be attached to the executive power (Executoriale Kracht).